Pemberdayaan Petani melalui Pengolahan Jerami Padi menjadi Sentra Pupuk Organik di Kampung Kuper Distrik Semangga Merauke - Erwin Nugraha Purnama; Apri Irianto; Mani Yusuf; Anwar Anwar; Abdul Rizal (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Kampung Kuper is a village in the Semangga District, Merauke Regency with a population of 1,298 people. This village is dominated by transmigration communities whose livelihoods are farmers. Kampung Kuper is a rice production center in Merauke Regency. The rice plants in this village are quite extensive so they have a lot of rice waste in the form of straw and husks that are not used and are left as waste and burned for further planting. Kampung Kuper also has chickens and cows whose dung can be used for organic fertilizer. Rice plant waste (straw, husk) and livestock manure (chicken, cow) are very important to be developed as organic fertilizers because they are rich in nutrients that plants need for growth and development. Based on the potential utilization of rice plant waste and livestock manure, this service activity is carried out to provide participation to farmer groups, especially motivating farmers in managing rice and livestock waste as organic fertilizer and making Kuper village a center for organic fertilizer production in Merauke Regency. The implementation of activities includes counseling and technical guidance as a medium for transferring knowledge and technology to partners, which will be carried out en masse, through groups and individuals. The solutions offered in the implementation of the Partner Village Development program are through non-physical and physical activities expected; 1) Provide counseling and technical guidance on the benefits of managing agricultural and livestock waste as organic fertilizer so that people care about environmental health and the food products they consume and 2) Assisting in the processing of rice straw and livestock manure as organic fertilizer. The community, especially farmer groups in Kuper Village, are very enthusiastic in participating in counseling activities as well as carrying out manufacturing practices